(untitled) ("Journal "U". Economy. Management. Finance.", 2020)
The article deals with the development of logistics innovations and substantiation of their role in the work of freight forwarding companies. It justifies the need for the use of logistic innovations in traffic flow management, the structure of the activities of forwarding companies, identified their strengths and weaknesses, summarizes the number of systems that improve the effectiveness of management.